Analisis SWOT Dalam Menentukan Strategi Pemasaran Pada Usaha Produk Olahan Ikan (Studi Kasus UMKM Sari Ulam Kota Tegal) - Istiana, Yulian; Utami, Suci Nur; Randi, Mohammad Jusuf; Adita, Muhammad Dini (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
This study aims to formulate an alternative competitive marketing strategy that is superior and the right company policy by identifying internal factors (strengths and weaknesses) and external factors (opportunities and threats) using the IFE and EFE analysis methods and in formulating alternative strategies that are applied with the SWOT matrix. The method used in this research is qualitative through interviews with business owners. The data collected includes primary and secondary data. The results showed that internal factors in terms of strength used quality raw materials with a score of (0,80), while the product design weaknesses are less attractive with a score of (0,80). External factors in terms of opportunities micro smalll and medium enterprises Sari Ulam has good relationships with business partners/reseller and has customer loyalty with a score a (1,00), while the threat is high business competition with a score of (0,60). These results place the position of the Sari Ulam UMKM in Tegal City in Quadrant I and the marketing strategy that must be applied is an aggressive growth strategy.